Rancang Bangun Sistem Monitoring Kualitas Air Tambak Udang (Litopenaeus Vannamei) Menggunakan Wireless Sensor Sistem (WSS) yang Terintegrasi dengan PLC CPM1A - Gurum Ahmad Pauzi; Okta Ferli Suryadi; Gregorius Nugroho Susanto; Junaidi Junaidi (Journal of Energy, Material, and Instrumentation Technology, 2020)
The research about pH, salinity, dissolved oxygen, and temperature monitoring system using Arduino Uno integrated with PLC CPM1A for water quality control of shrimp farm litopenaeus vannamei had done. The system used pH meter kit Dfrobot sensor, salinity sensor, DS18B20 waterproof sensor, and analog dissolved oxygen sensor which was controlled by Arduino UNO. In order to calibrate the sensor, pH meter kit Dfrobot sensor was calibrated by using a buffer solution, salinity sensor was calibrated by refractometer, DS18B20 waterproof sensor was calibrated by HTC-02 thermometer, and an analog dissolved oxygen sensor was calibrated by DO meter YSI 55. The results showed that the sensors can detect pH, salinity, dissolved oxygen and temperature with accuracy 94.06%, 78.15%, 90.53% and 99.42% respectively. It is transmitted wireless by using the nRF24l01+ module. The furthest distance in the line of sigh test was 405 meters and in non-line of sigh was 163 meters. The measurement had done 3 times per day (morning, afternoon, evening) in 3 days. The relay also can be integrated with PLC CPM1A to control the wheel and water pump.